The global lives of things the material culture of connections in the early modern world - Gerritsen, Anne; Riello, Giorgio (Routledge, 2016)
"The Global Lives of Things considers the ways in which 'things,' ranging from commodities, to works of art and precious materials, participated in the shaping of 'globalisation' in the early modern period. This volume traces the movements of objects through human networks of commerce, colonialism and curiosity. It argues that material objects mediated between the forces of global economic exchange and the constantly changing identities of individuals, as they were drawn into global circuits"--Provided by publisher.